A retrospective study of 157 hospitalized cats with pancreatitis in a tertiary care center: Clinical, imaging and laboratory findings, potential prognostic markers and outcome. (13th October 2018) - Nivy, Ran; Kaplanov, Alina; Kuzi, Sharon; Mazaki‐Tovi, Michal; Yas, Einat; Segev, Gilad; Ben‐Oz, Jennifer; Lavy, Eran; Aroch, Itamar
Abstract : Background: Pancreatitis in cats (FP) has been increasingly diagnosed in recent years, but clinical studies of large numbers of affected cats are scarce. Objectives: To describe a large cohort of cats with FP requiring hospitalization. Animals: One hundred and fifty‐seven client‐owned cats. Methods: Retrospective study, including cats diagnosed with pancreatitis based on sonographic evidence, positive SNAP feline pancreatic lipase immunoreactivity test results, increased 1, 2‐o‐dilauryl‐rac‐glycerol‐glutaric Acid‐(6′‐methylresorufin ester)‐lipase activity, histopathology, or some combination of these. Results: One‐hundred and twenty‐two cats (77.7%) survived to discharge. Median time from onset of clinical signs to presentation was longer ( P = .003) in nonsurvivors. Causes of FP included recent general anesthesia, trauma, hemodynamic compromise, and organophosphate intoxication, but most cases (86.6%) were idiopathic. Ultrasonographic findings consistent with pancreatitis were documented in 134 cats, including pancreatomegaly (81.3%), decreased (31.3%), or increased (14.9%) pancreatic echogenicity, extra‐hepatic biliary tract dilatation (24%), and increased peri‐pancreatic echogenicity (13%). Lethargy ( P = .003), pleural effusion ( P = .003), hypoglycemia ( P = .007), ionized hypocalcemia ( P = .016), azotemia ( P = .014), parenteral nutrition administration ( P = .013), and persistent anorexia during hospitalization ( P = .001) were more frequent in nonsurvivors, whereas antibiotics were more frequently administered to survivors ( P = .023). Nevertheless, when Bonferroni's correction for multiple comparisons was applied, none of the variables was statistically significant. Conclusions and Clinical Importance: Previously unreported, clinically relevant, potential prognostic factors, including hypoglycemia, azotemia, parenteral nutrition, and withholding antibacterial treatment were identified in this exploratory study. These preliminary results should be examined further in confirmatory studies.